Bioprinting and regeneration of auricular cartilage using a bioactive bioink based on microporous photocrosslinkable acellular cartilage matrix - Litao Jia; Yujie Hua; Jinshi Zeng; Wenshuai Liu; Di Wang; Guangdong Zhou; Xia Liu; Haiyue Jiang (Bioactive Materials, 2022)
Tissue engineering provides a promising strategy for auricular reconstruction. Although the first international clinical breakthrough of tissue-engineered auricular reconstruction has been realized based on polymer scaffolds, this approach has not been recognized as a clinically available treatment because of its unsatisfactory clinical efficacy. This is mainly since reconstruction constructs easily cause inflammation and deformation. In this study, we present a novel strategy for the development of biological auricle equivalents with precise shapes, low immunogenicity, and excellent mechanics using auricular chondrocytes and a bioactive bioink based on biomimetic microporous methacrylate-modified acellular cartilage matrix (ACMMA) with the assistance of gelatin methacrylate (GelMA), poly(ethylene oxide) (PEO), and polycaprolactone (PCL) by integrating multi-nozzle bioprinting technology. Photocrosslinkable ACMMA is used to emulate the intricacy of the cartilage-specific microenvironment for active cellular behavior, while GelMA, PEO, and PCL are used to balance printability and physical properties for precise structural stability, form the microporous structure for unhindered nutrient exchange, and provide mechanical support for higher shape fidelity, respectively. Finally, mature auricular cartilage-like tissues with high morphological fidelity, excellent elasticity, abundant cartilage lacunae, and cartilage-specific ECM deposition are successfully regenerated in vivo, which provides new opportunities and novel strategies for the fabrication and regeneration of patient-specific auricular cartilage.